Optofluidic microengine in a dynamic flow environment via self-induced back-action - Shi, Yuzhi (2021)
Most existing optofluidic particle engines only operate in a static environment. Here, we present a four-energy-state optofluidic microengine that operates stably in a dynamic flow environment, a function unattainable by existing systems due to the disturbance of the fluidic drag force. This microengine is powered synergistically by both the optical force and fluidic drag force, and it exploits the intriguing behavior of the particle in an asymmetric two-dimensional light interference pattern under the self-induced back-action (SIBA) effect. The mechanism of the microengine is studied in detail, and a microengine comprising a single cell and a cell-particle complex has been demonstrated. Our optofluidic microengine is the first of its kind to operate in the dynamic flow environment, and it provides a new platform to study single cell dynamics and cell-particle or cell-cell interactions in the dynamic fluidic environment.